Influence of the Wheels on the Automobile Dynamics - Rastislav Istenik; Dalibor Barta; Wladyslaw Mucha (Communications - Scientific letters of the University of Zilina, 2019)
The analysis of the vehicle dynamics with various types of wheels (R13, R14, R15) in two shifting modes and at the driving on a horizontal plane, at downhill- and uphill- driving as well as with different vehicle total mass is described in this paper.